2001
DOI: 10.1159/000052478
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between the Amount of Tissue Removed at Transurethral Resection of the Prostate and Clinical Improvement in Benign Prostatic Hyperplasia

Abstract: Objective: To assess in a prospective trial the influence of the amount of tissue resected at transurethral resection of the prostate (TURP) for benign prostatic enlargement on the symptom improvement as assessed by symptom scores. Methods: Between December 1996 and August 1998 a total of 138 men (mean age 68.2, range 53–89) with symptomatic benign prostatic enlargement who underwent TURP participated in this prospective study. Patients were assessed preoperatively with the International Prostate Symptom Score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 15 publications
5
25
1
3
Order By: Relevance
“…While some authors have suggested that better clinical results after TURP may correlate with the completeness of the resection of the obstructing adenoma (9,10), others have shown that partial resection produces short-term functional results comparable to those of standard TURP (11,12). The aim of this study was to evaluate the impact of the percent of resected tissue (PRT) during TURP on the short-term clinical outcome of patients with LUTS due to BPH.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors have suggested that better clinical results after TURP may correlate with the completeness of the resection of the obstructing adenoma (9,10), others have shown that partial resection produces short-term functional results comparable to those of standard TURP (11,12). The aim of this study was to evaluate the impact of the percent of resected tissue (PRT) during TURP on the short-term clinical outcome of patients with LUTS due to BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested complete resection should be performed for better result. 19,20 while others have suggested that a partial resection is adequate for short term functional results. 21,22 The recommended TURP technique consists of a complete resection of adenomatous tissue inside the surgical capsule for better result in terms of quality of life and symptom improvement.…”
mentioning
confidence: 99%
“…Hakenberg O et al 2001 30 también utilizaron el cuestionario BII, entre otras medidas, para evaluar el grado de mejoría de los síntomas de la HBP en pacientes en los que se había practicado una resección transuretral de próstata. Concretamente el BII se administró antes y después de la intervención a los 3 y 6 meses.…”
Section: Discussionunclassified